Microbial mechanisms underlying the reduction of N2O emissions from submerged plant covered system - Yongxia Huang; Min Deng; Shuni Zhou; Yunpeng Xue; Senbati Yeerken; Yuren Wang; Lu Li; Kang Song (Water Research X)
Submerged plant (SP) restoration is a crucial strategy for restoring aquatic ecosystem. However, the effect of SP on nitrous oxide (N2O) emissions remains controversial, and the impact of SP-attached biofilms on N2O emissions is often overlooked. In this study, SP and non-submerged plant (NSP) systems were set up and operated continuously for 189 days, revealing that SP reduced N2O flux by 42.4 %. By comparing the N2O net emission rates from water, sediment, and biofilms, we identified biofilms as the primary medium responsible for the reduction in N2O emissions in both SP and NSP systems. Further analysis of N2O metabolic rates from nitrification, denitrification, and abiotic processes under light and dark conditions confirmed that counter-diffusion of dissolved oxygen and nutrients in SP biofilms plays a key role in reducing denitrification-driven N2O emissions. Additionally, SP-attached biofilms increased nosZII-type denitrifiers (e.g., Bacillus) and reduced N2O production potential ((nirS+nirK)/(nosZI+nosZII)). Notably, the establishment of a SP restoration project in a typical eutrophic freshwater lake demonstrated that SP could reduce N2O fluxes by 61.5 %. This study provides significant insights for strategies aimed at mitigating N2O emissions.